2014
DOI: 10.1093/femspd/ftu020
|View full text |Cite
|
Sign up to set email alerts
|

Mce4F Mycobacterium tuberculosis protein peptides can inhibit invasion of human cell lines

Abstract: This work was aimed at studying the Mycobacterium tuberculosis H37Rv Rv3494c protein, taking into account that it belongs to the mammalian cell entry family (mce) which is thought to have important functions in the disease's pathogenesis. The protein was characterized in silico; its presence on mycobacterial surface was confirmed by immunoelectron microscopy. High-activity binding peptides (HABPs) were identified by binding assays with (125)I; their ability to inhibit mycobacterial entry to two cell lines (U93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The disruption of mce4 results in failure of M. tuberculosis to maintain chronic infection in mice, while retaining full virulence during the acute phase ( Mohn et al, 2008 ; Pandey and Sassetti, 2008 ). In contrast to these findings, the MCE family protein and the Mce-associated protein are generally considered as virulence factors, and are associated with lipid transport and host cell invasion ( Rodriguez et al, 2015 ; Perkowski et al, 2016 ). Ag85B may also contribute to the adherence, invasion, and dissemination of organisms in the host tissue, which can bind to Fn and play a critical role in mycobacterial adherence to the host cells ( Kassa et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…The disruption of mce4 results in failure of M. tuberculosis to maintain chronic infection in mice, while retaining full virulence during the acute phase ( Mohn et al, 2008 ; Pandey and Sassetti, 2008 ). In contrast to these findings, the MCE family protein and the Mce-associated protein are generally considered as virulence factors, and are associated with lipid transport and host cell invasion ( Rodriguez et al, 2015 ; Perkowski et al, 2016 ). Ag85B may also contribute to the adherence, invasion, and dissemination of organisms in the host tissue, which can bind to Fn and play a critical role in mycobacterial adherence to the host cells ( Kassa et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…Receptor‐ligand binding assays were used for identifying Rv3705c peptides having high specific binding ability; this involved labelling each peptide with Na 125 I according to the techniques described by Yamamura [Yamamura et al, ], as reported in previous studies [Ocampo et al, , ,; Rodriguez et al, ]. Then 1.5 × 10 6 cells were placed per well in 96‐well dishes, in triplicate, for evaluating specific binding to the U937 and A549 cell lines and incubated at 4 °C (U937) and 37 °C (A549) for 2 h with increasing concentrations of radiolabeled peptide (0–950 nM) in the presence (inhibited binding) and absence (total binding) of the same non‐radiolabeled peptide at 40 μM concentration.…”
Section: Methodsmentioning
confidence: 99%
“…2013; Rodriguez et al. 2015). The mce genes are also present in other species like Nocardia , Janibacter , Nocardiodes , Amycolatopsis and Streptomyces (Table 1) as well as in Gram-negative bacteria and have also been found encoded in plant genomes.…”
Section: Introductionmentioning
confidence: 99%
“…2005; Rodriguez et al. 2015). As the mce genes are absent in the human genome, these genes might also be represented as ideal candidates for drug targets (Zhang and Xie 2011).…”
Section: Introductionmentioning
confidence: 99%